BUSINESS MANAGEMENT TRAINING FOR UMKM ACTORS IN BALESARI VILLAGE, WINDUSARI DISTRICT, MAGELANG REGENCY - Hanung Eka Atmaja; Satrio Tegar Sadewo; Yesica Apriliana Paska; Miftachul Mujib; Sofyan Ashari Nur; Ipuk Widayanti (RADJA PUBLIKA, 2024)
The community service program carried out in Balesari Village, Windusari District, Magelang Regency aims to identify the obstacles or problems experienced by MSME actors so that the problems can be identified which can then be used as coaching material in each MSME so that MSMEs can develop and encourage the economy of the surrounding community. The methods used are counseling, tutorials and discussions. Human Resources (HR) in an organization is a very important element. MSMEs really need superior HR in knowledge and skills about business management to manage their businesses for the progress of their businesses. Therefore, MSME managers are expected to have the skills to manage their business operations, as well as manage facilities and infrastructure in their businesses. When MSME managers have good business management knowledge, it will make it easier for their businesses to continue to develop and run dynamically and flexibly in facing all the demands of changing times. Therefore, the activities carried out in this community service are by assisting MSME actors, especially related partners, to develop their businesses so that they are able to compete with other MSMEs by holding training, delivering materials, and mentoring on business management which includes marketing management , innovation and product development and technology and information management. Partners are assisted by the community service team to carry out business management and use technology properly to expand the market and increase product appeal to win market competition.practices.